3D Bioprinting Strategies for Melatonin‐Loaded Polymers in Bone Tissue Engineering - Damla Aykora; Ayhan Oral; Cemre Aydeğer; Metehan Uzun (Macromolecular Materials and Engineering)
Abstract Bone pathologies are still among the most challenging issues for orthopedics. Over the past decade, different methods are developed for bone repair. In addition to advanced surgical and graft techniques, polymer‐based biomaterials, bioactive glass, chitosan, hydrogels, nanoparticles, and cell‐derived exosomes are used for bone healing strategies. Owing to their variation and promising advantages, most of these methods are not translated into clinical practice. Three dimensonal (3D) bioprinting is an additive manufacturing technique that has become a next‐generation biomaterial technique adapted for anatomic modeling, artificial tissue or organs, grafting, and bridging tissues. Polymer‐based biomaterials are mostly used for the controlled release of various drugs, therapeutic agents, mesenchymal stem cells, ions, and growth factors. Polymers are now among the most preferable materials for 3D bioprinting. Melatonin is a well‐known antioxidant with many osteoinductive properties and is one of the key hormones in the brain–bone axis. 3D bioprinted melatonin‐loaded polymers with unique lipophilic, anti‐inflammatory, antioxidant, and osteoinductive properties for filling large bone gaps following fractures or congenital bone deformities may be developed in the future. This study summarized the benefits of 3D bioprinted and polymeric materials integrated with melatonin for sustained release in bone regeneration approaches.